“We just Go with the Flow”: Healthcare Providers as Secondary Impacted Subjects in Informal Refugee Healthcare Provision in Indonesia - Masardi, Realisa D; Lazuardi, Elan (Masyarakat: Jurnal Sosiologi, 2025)
With prolonged transit times, refugees’ right to health in Indonesia has become an urgent issue. This article asks how healthcare providers are positioned within Indonesia’s ambiguous refugee health provision regime. Drawing on qualitative fieldwork, this study moves beyond a legalistic analysis of refugee health rights by foregrounding the precarious positions of healthcare providers themselves. We examine Presidential Regulation 125/2016 as well as state and non-state actors’ views on what are often described as structural barriers in improving refugees’ rights. We argue that conditions of informality, which both arise from and perpetuate institutional ambiguity, systematically undermine refugees’ right to health while simultaneously constraining healthcare providers’ authority and capacity to act. These dynamics contribute to the reproduction of an unjust migration regime in which healthcare providers are compelled to operate within severely limited referral and decision-making frameworks.